Photovoltaic Cells: Principles of Operation and Performance Characteristics - Abdulgader Alsharif; Fathallah I. Solman; Abdelgader Agilah Saleh Gheidan; Abdussalam Ali Ahmed; Llahm Omar Farag Ben Dalla; Mohamed A. Alsharif; Abba Lawan Buker; Ibrahim Imbayah (Journal of Scientific and Human Dimensions, 2026)
Photovoltaic cells are among the most important technologies for converting solar energy into electricity, relying on the photovoltaic effect in semiconductor materials such as silicon. When sunlight strikes the cell, photons are absorbed, transferring their energy and releasing electrons, thereby generating an electric current. Cells are manufactured in several types: monocrystalline and polycrystalline silicon, thin films (e.g., CdTe, CIGS), and emerging technologies (such as perovskite and multi-junction cells). Cell efficiency is measured by key performance parameters: open-circuit voltage (Voc), short-circuit current (Isc), fill factor (FF), and efficiency (η). These parameters are influenced by solar irradiance intensity, temperature, and material properties. Photovoltaic cells contribute to advancing renewable energy and reducing emissions, with ongoing research aimed at improving their efficiency and lowering costs